Arabic Hate Speech in Youtube Al-Jazeera Comments on The Death of Ismail Haniyeh: Forensic Linguistic Studies - Sa'baniyah, Hanania; Zawawi, Moh; Rifki Mustofa; Ahmad Arifin (Modality Journal: International Journal of Linguistics and Literature, 2025)
The Israel–Palestine conflict escalated once again in early October 2023, resulting in numerous casualties. One incident that drew international attention was the reported death of Ismail Haniyeh, a senior Hamas leader, who was allegedly killed in Tehran by a blast believed to have been launched by Israel. This event sparked widespread public reaction, especially on digital platforms such as YouTube. This study examines Arabic-language hate speech found in the comment section of a news video uploaded by @Al-Jazeera Arabic covering Haniyeh’s death. Using a forensic linguistics framework within a media discourse analysis approach, the study applies a qualitative descriptive method, with data collected through reading and note-taking techniques. The primary data were obtained from user comments on the YouTube video posted by @Al-Jazeera Arabic, specifically concerning the case of Ismail Haniyeh’s death. The analysis identifies hate speech based on expressions that contain insults, hostility, or incitement, categorized linguistically. He findings reveal six referents of hate speech, namely: circumstances (6 hate speech), objects (7 hate speech), activities (4 hate speech), kinship (3 hate speech), profession (2 hate speech), exclamation (2 hate speech). In terms of the linguistic forms used, hate speech is found in the form of words, phrases, and clauses, namely there are 6 hate speech words, 9 hate speech phrases, and 9 hate speech clauses. The study highlights how hate speech in digital discourse reflects not only emotional reactions but also the linguistic strategies users employ to express ideological and political stances.